Distance choral conducting training of future music teachers - Gulnaz Nailevna Akbarova (Política e Gestão Educacional, 2021)
The article reflects the study results, the purpose of which is to identify the distance approach's educational potential and determine its role in the conduct and choral training of a future musician teacher. The study examines the situation in the conduct and choral training of a future musician teacher, identifies the problems, and compares traditional and modern methodology. The study was conducted based on the Institute of Philology and Intercultural Communication of Kazan Federal University in three stages. It was based on the integrated application of literature analysis and practical experience, the study of teaching materials, pedagogical monitoring, and pedagogical experience generalization. During the distance approach application analysis in the educational practice of Kazan Federal University, they determined the conditions for the distance format implementation in conduct and choral training: provision with the material and technical base and special methodological support in the form of digital educational resources in conduct and choral disciplines; the availability of specialist teaching aids for independent conduct and choral training and the possibility of receiving distance pedagogical advice. The effectiveness of conduct and choral training is determined by the balanced use of contact and distance learning with a well-defined education strategy and methodological support.